Displacement response characteristics of different sand tunnel excavation faces under true triaxial loading - Li, Erchao; Gao, Quanchen; Li, Xiao; Mao, Tianqiao; Zheng, Bo (Frontiers in Earth Science, 2023)
During the construction of subway tunnels, the geotechnical body is affected by excavation to produce three-dimensional spatial deformation. The deformation of geotechnical bodies is an important safety hazard for project advancement, so it is important to understand the excavation disturbance range and deformation mechanism. The current related research is mainly about the theory of land subsidence and the two-dimensional plane displacement of the stratum, and there are few studies on the specific three-dimensional disturbance mode and its mechanism. In order to better understand the three-dimensional displacement characteristics of the tunnel excavation soil, a tunnel excavation model test was established based on a true triaxial stress loading system combined with three-dimensional scanning technology for a superimposed sandy soil. Based on the established model, the vector displacement response range and three-dimensional deformation characteristics of the excavation face were studied in the main displacement affected area around the excavation face. Meanwhile, the deformation characteristics, such as vertical settlement and horizontal displacement of the stratum in the main influence area were analyzed. The results show that the main influence area of tunnel excavation is elliptical and distributed within a range of twice the diameter of the tunnel axis. The main influence range is bell-shaped in the vertical direction and inverted wedge-shaped in the horizontal direction. The three-dimensional space presents a "W" deformation distribution. The three-dimensional deformation theoretical model of the excavation face established in this paper can provide some references for the excavation engineering of superimposed sand-soil tunnels.